2011
DOI: 10.1007/s00198-011-1824-6
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular bone score (TBS): available knowledge, clinical relevance, and future prospects

Abstract: The diagnosis of osteoporosis rests on areal bone mineral density (BMD) measurement using DXA. Cancellous bone microarchitecture is a key determinant of bone strength but cannot be measured using DXA. To meet the need for a clinical tool capable of assessing bone microarchitecture, the TBS was developed. The TBS is a texture parameter that evaluates pixel gray-level variations in DXA images of the lumbar spine. The TBS variations may reflect bone microarchitecture. We explain the general principles used to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
0
11

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(134 citation statements)
references
References 15 publications
3
120
0
11
Order By: Relevance
“…This is consistent with the 1.45% CV reported by Krueger et al [24] for the L1-L4 ROI in a comparable precision study on GE Lunar Prodigy. The limited information on in vivo reproducibility available from Bousson et al [19] demonstrated a 1.2%…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is consistent with the 1.45% CV reported by Krueger et al [24] for the L1-L4 ROI in a comparable precision study on GE Lunar Prodigy. The limited information on in vivo reproducibility available from Bousson et al [19] demonstrated a 1.2%…”
Section: Discussionmentioning
confidence: 97%
“…Higher body mass index (BMI) has been demonstrated to contribute to increased DXA precision error that may be attributable to greater tissue inhomogeneity at the site of the lumbar spine and a reduction in signal to noise ratio in larger participants [17] . Whilst short-term precision has been reported for DXA BMD measurement [18,22] information is very limited regarding in vivo short-term precision error (STPE) for TBS [19] . This study investigated the STPE of TBS and BMD and the effect of obesity on precision error.…”
mentioning
confidence: 99%
“…The trabecular bone score (TBS) is a grey-level texture measurement based on the use of experimental variograms of two-dimensional (2D) projection images acquired during a dual-energy X-ray absorptiometry (DXA) lumbar spine (LS) scan (13). It may be used for the routine evaluation of bone micro-architecture, as it is strongly correlated with bone micro-architecture, regardless of BMD (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…TBS provides an alternative measurement of bone architecture using DXA scan images. Using pixel-by-pixel analysis of DXA scans of the lumbar spine, TBS provides an analogue of trabecular bone structure that has been demonstrated to predict fracture risk independently of BMD [30,31]. However, this has been demonstrated to have a higher precision error in an obese population [32].…”
Section: Current Diagnostic Methodsmentioning
confidence: 99%